PENGAWASAN TERHADAP PERLINDUNGAN HUKUM KONSUMEN PERBANKAN OLEH OTORITAS JASA KEUANGAN DI KOTA PADANG - Zulkifli, Zulkifli; Fauzi, Wetria; Pratama, Arya Putra Rizal (Jurnal Hukum Bisnis Bonum Commune, 2022)
Supervison against banking industry not only supervise by Supervision aouthority, nevertheless have to completely by internal dan discipline supervision. Nessecity about regulation colleration with bank supervision about conduct business supervision to focus safety consument as for client cause cheating dan unfair that possibility happen against conduct for businessmen in financial sector. Market conduct is businessmen behaviour in financial sector for design, arrangement,and giving a information, supplying, making a agreement to product and service and dispute settlement and complain help. Research result to explain so, protection against bank consument to basically with contract or agreement and law enforcement via litigation or non-litigation. After that, Implementation against law protection for consument steady to supervision if some financial aouthority have obstacle or difficult to improving a performance by standart parameter. And then, Human Resource in Financila Authority Republic of Indonesia have problem and also huge pressure in task of OJK in beside of micro prudential supervision and also Conduct Business Supervision